A hybrid approach for deriving horizontal site amplification factors considering both the similarity of HVSRE and the vertical amplification correction function. (14th October 2022) - Wang, Ziqian; Nakano, Kenichi; Ito, Eri; Kawase, Hiroshi; Matsushima, Shinichi
Abstract: Under hypothetical and idealized conditions, the horizontal site amplification factor (HSAF) is defined as the ratio of the horizontal Fourier amplitude spectrum (FAS) at a point on the Earth's surface with respect to the horizontal FAS at the identical location but on the outcropping seismological bedrock. The HSAF reflects the profile of local sedimentary soils and weathered rock formations, indicating site effects. In most cases, such an idealized HSAF is difficult to measure directly. Thus, quantitatively estimating a HSAF value is a crucial task in strong‐motion prediction over the last century. Fortunately, many strong‐motion stations have been constructed throughout Japan, facilitating the characterization of HSAFs down to seismological bedrock at more than 1600 observational sites by the generalized inversion technique (GIT). First, this study reported the similarity distribution of the HSAF and the horizontal‐to‐vertical spectral ratio of earthquakes (HVSRE ). Subsequently, we proposed a hybrid method from a novel aspect for estimating HSAF in terms of the observed similarity distribution and the vertical amplification correction function (VACF) proposed previously. Compared with the direct use of HVSRE for substituting HSAF, the hybrid method proposed herein demonstrated an improvement of greater than 30% in terms of the residuals between estimated HSAFs and those separated from observations.